2020
DOI: 10.3389/fmicb.2020.01980
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Way Road: Antagonistic Interaction Between Dual-Species Biofilms Formed by Candida albicans/Candida parapsilosis and Trichophyton rubrum

Abstract: Dermatomycoses include superficial fungal infections of the skin and its appendages. Trichophyton rubrum, Candida albicans, and Candida parapsilosis are some of the most prevalent species that cause dermatomycoses. Several studies show a variable predominance of Candida spp. in relation to dermatophytes, especially in onychomycosis and the possibility of isolating both from the same site. The ability of dermatophytes to form biofilms recently been explored and there is currently no evidence on the involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…The data revealed that Δ stuA mutant had a different kinetic of mature biofilm formation and marked differences in hyphal development compared to wild-type T. rubrum ( Figures 4A, B ). In the wild-type strain, a significant increase in metabolic activity was observed at 72 h, with a slight increase at 96 h, followed by an activity decay at 120 h ( Figure 4C ), consistent with previous data ( Garcia et al., 2020 ). In contrast, in the Δ stuA strain, an increase in metabolic activity was only detected at 120 h ( Figure 4D ).…”
Section: Resultssupporting
confidence: 92%
“…The data revealed that Δ stuA mutant had a different kinetic of mature biofilm formation and marked differences in hyphal development compared to wild-type T. rubrum ( Figures 4A, B ). In the wild-type strain, a significant increase in metabolic activity was observed at 72 h, with a slight increase at 96 h, followed by an activity decay at 120 h ( Figure 4C ), consistent with previous data ( Garcia et al., 2020 ). In contrast, in the Δ stuA strain, an increase in metabolic activity was only detected at 120 h ( Figure 4D ).…”
Section: Resultssupporting
confidence: 92%
“…All strains were obtained from the Clinical Mycology Laboratory of the Department of Clinical Analysis, Faculty of Pharmaceutical Sciences-UNESP, Brazil. Microorganisms were grown on malt extract agar [malt extract (Kasvi): 2%, peptone from animal tissue ( Sigma-Aldrich ): 2%, glucose ( Synth ): 2% and agar (Kasvi): 2%], pH 5.7, incubated at 28°C for 7 days or until sporulation ( Garcia et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that biofilms by dermatophytes in vitro mature after 72 h, although variations between different strains have also been reported (Costa-Orlandi et al, 2014;Brilhante et al, 2017;Chen et al, 2019;Costa-Orlandi et al, 2020;Garcia et al, 2020). The ability of NO-np to inhibit biofilm formation when coincubated with planktonic cells and to damage established biofilms was evaluated and compared to FCZ, TRB and EFCZ.…”
Section: Discussionmentioning
confidence: 99%
“…While typically involving the stratum corneum in healthy individuals, follicular and dermal invasion can occur in various clinical scenarios, such as immunosuppression, and can be a portal for polymicrobial infections (de Sousa Mda et al, 2015;Gupta et al, 2017;Pereira, 2021). The ability of these fungi to form biofilms has been widely studied in recent years (Costa-Orlandi et al, 2014;Brilhante et al, 2017;Costa-Orlandi et al, 2017;Danielli et al, 2017;Chen et al, 2019;Costa-Orlandi et al, 2020;Garcia et al, 2020;Bila et al, 2021). Biofilm formation by dermatophytes, especially in the setting of onychomycosis (Burkhart et al, 2002;Gupta et al, 2016;Lipner and Scher, 2019;Gupta and Foley, 2019), further complicates and limits current treatment strategies, as they are highly resistant to antimicrobials (Ramage et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation